The ecology and breeding biology of the Gemsbok (Oryx Gazella Gazella) (Linnaeus, 1785) in the Hester Malan Nature Reserve - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 1980.